PEMBERDAYAAN MASYARAKAT DESA MOJOPURNO MELALUI PELATIHAN PEMBUATAN SABUN DARI LIMBAH MINYAK JELANTAH - Prabowo, Sigit Ari; Ardhi, Muh. Waskito; Sasono, Mislan (Jurnal Terapan Abdimas, 2016)
Jelantah oil is used cooking oil waste, this is organic but if mishandled will pollute the environment. Cooking oil is used for frying foods optimum for 4 times the pan. Cooking oil after use more than 4 times the Pan contains a very high cholesterol levels so that harm to human health that consume them. The purpose this implementation to provide training on the utilization of jelantah from Pan crackers at factory crackers Mojopurno for make an organic soap alternatives. Outreach activities are divided into three phases : 1) observation phase, carried out to determine the potential spread of the villagers and the mojopurno primarily citizens around factories manufacturing crackers; 2) stage of training, was implemented to provide skills training through the creation of soap from the raw material of oil jelantah; 3) Stage evaluation, conducted an evaluation the activities of the citizens who have obtained training in the utilization of waste oil jelantah for making soap.Keywords: Jelantah, Soap, Mojopurno